Preliminarna analiza in restavriranje pahljač za razstavo Pod Napoleonovim orlom v Narodnem muzeju Slovenije - Pajagič Bregar, Gojka (Etnolog. Nova vrsta (Ljubljana), 2009)
The author presents the origin and development of fans in different periods and environments. The two fans from the collection of the National Museum of Slovenia, which were analysed, restored and conserved for the exhibition Under Napoleon''s Eagle, date from the turn of the 19th century. The article first describes the fans in detail, followed by the results and interpretationof the EDS XRF and microscopic analyses, performed at the laboratory of the National Museum of Slovenia, and a description and interpretation of the conservation and restoration procedures. It concludes with recommendations for exhibiting the fans and storing them in the museum depot.
Keywords: Narodni muzej Slovenije (Ljubljana); muzeji; muzejske zbirke; restavriranje; konserviranje; pahljače